2011
DOI: 10.1109/tnsre.2011.2168981
|View full text |Cite
|
Sign up to set email alerts
|

Object Manipulation Improvements Due to Single Session Training Outweigh the Differences Among Stimulation Sites During Vibrotactile Feedback

Abstract: Most hand prostheses do not provide intentional haptic feedback about movement performance; thus users must rely almost completely on visual feedback. This paper focuses on understanding the effects of learning and different stimulation sites when vibrotactile stimulation is used as the intentional haptic feedback. Eighteen unimpaired individuals participated in this study with a robotic interface to manipulate a virtual object with visual and vibrotactile feedback at four body sites (finger, arm, neck, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…Appropriate sites on the body for the vibrators must be found; for example, the vibration must be easy to perceive, and at the same time, the vibrators should not hinder movement. Interestingly, some sites might have an initial advantage in representing specific information, due to its naturalness; however, the advantage dissolves when users are given enough time to become familiar with less intuitive sites (Stepp & Matsuoka, 2011). Moreover, appropriate signal ranges and modulations (e.g., pulse or amplitude modulation) of the vibration must be evaluated (Stepp & Matsuoka, 2012).…”
Section: Vibrotactile Feedback Systems Need To Be Evaluated In Motor mentioning
confidence: 99%
“…Appropriate sites on the body for the vibrators must be found; for example, the vibration must be easy to perceive, and at the same time, the vibrators should not hinder movement. Interestingly, some sites might have an initial advantage in representing specific information, due to its naturalness; however, the advantage dissolves when users are given enough time to become familiar with less intuitive sites (Stepp & Matsuoka, 2011). Moreover, appropriate signal ranges and modulations (e.g., pulse or amplitude modulation) of the vibration must be evaluated (Stepp & Matsuoka, 2012).…”
Section: Vibrotactile Feedback Systems Need To Be Evaluated In Motor mentioning
confidence: 99%
“…In a recent study, eighteen unimpaired individuals participated for 2.5–4 hours using this interface to manipulate a virtual object with visual and vibrotactile feedback at four body sites (finger, arm, neck, and foot), presented in a random order [25]. We found that the effects of learning over the course of the experiment overshadowed the effects of supplying feedback at different stimulation sites.…”
Section: Introductionmentioning
confidence: 84%
“…We used a previously-designed robotic and virtual interface to study object manipulation in which both visual, direct haptic, and vibrotactile feedback could be experimentally controlled [25]. This virtual task allowed us to study the effects of vibrotactile feedback as a substitute for typical, direct force feedback in healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Simple tasks such as reach, grasp, or object manipulation that employ both visual and tactile/haptic feedback have shown the most promising effects of multimodal feedback [26-28, 32, 33], while other studies have shown deterioration of performance [15, 30, 31]. Specifically, Rosati et al [34] found that combining auditory and visual feedback resulted in improved performance during learning of tracking motion exercises.…”
Section: Introductionmentioning
confidence: 99%